2019
DOI: 10.1177/0049124119852384
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Blackbox of Treatment Interference: Tracing Treatment Diffusion through Network Analysis

Abstract: Causal inference under treatment interference is a challenging but important problem. Past studies usually make strong assumptions on the structure of treatment interference in order to estimate causal treatment effects while accounting for the effect of treatment interference. In this article, we view treatment diffusion as a concrete form of treatment interference that is prevalent in social settings and also as an outcome of central interest. Specifically, we analyze data from a smoking prevention intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…A revealing example of how information spreads through networks and thereby affects non-treated subjects comes from a smoking-prevention intervention study. Regarding interference itself as the outcome of interest, the study showed how friendship ties significantly increased the log odds of receiving information from an intervention brochure (An and VanderWeele 2019). Whilst interference is a nuisance in many research settings when it violates the SUTVA, it is here the outcome of interest.…”
Section: Analyzing Outcomes Of Network Tiesmentioning
confidence: 98%
“…A revealing example of how information spreads through networks and thereby affects non-treated subjects comes from a smoking-prevention intervention study. Regarding interference itself as the outcome of interest, the study showed how friendship ties significantly increased the log odds of receiving information from an intervention brochure (An and VanderWeele 2019). Whilst interference is a nuisance in many research settings when it violates the SUTVA, it is here the outcome of interest.…”
Section: Analyzing Outcomes Of Network Tiesmentioning
confidence: 98%
“…Therefore, some researchers have developed novel methodologies to account for spillovers in a more general setting, where units interfere according to the links observed over a network (general or network interference) both in experimental settings (Aronow and Samii, 2017;Athey et al, 2018;Leung, 2020b;Bargagli Stoffi et al, 2020;Imai et al, 2020) and in observational studies (Ogburn et al, 2017;Sofrygin and van der Laan, 2017;Forastiere et al, 2018Forastiere et al, , 2020bTortù et al, 2020). These estimators tackle the problem of interference without distinguishing between the specific underlying mechanisms (An and VanderWeele, 2019). In the presence of treatment diffusion, these methods would estimate the causal effects of the initial treatment assignments, including the spillover effects from the treatment assigned to other units.…”
Section: Related Literaturementioning
confidence: 99%
“…Very few works explicitly deal with treatment diffusion An and VanderWeele, 2019). However, the existing works on treatment diffusion assume to have perfect knowledge on both the baseline social network describing relations among units and the actual treatment diffusion network describing who passes the treatment to whom over time.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations